Hukum Pidana terhadap Pemaksaan Anak sebagai Pengemis terkait Undang-Undang Kesejahteraan Anak - Nabila Dwi Elsa (Bhirawa Law Journal, 2022)
Regarding the increasing number of underage beggars, it is motivated by individuals who force children to work as beggars by instilling in children that working is easier and earning money than taking proper education in accordance with their rights as children, as stated in Article 5 paragraph (1) The Child Protection Act, which states "every citizen has the same right to obtain a quality education", therefore it is necessary to make efforts to build human awareness of the rights to education of children that must be obtained and professions or jobs for adults which have also been guaranteed. by the constitution.